Acordos para cooperação acadêmica Internacional: análise e proposta técnico-administrativa para uma instituição de ensino superior. - Paiva, Raquel Soprani dos Santos (2019)
Following the importance of documentary and procedural standards in public institutions, including those of higher education, as they serve society in the fields of teaching, research and extension, this study aimed to present analysis and proposal for organization and order of process flow of technical and administrative procedures for formalizing general agreements for international academic cooperation, uniting documentary and procedural models. The research problem is what is the process and document model for general agreements for international academic cooperation within Brazilian public higher education institutions? The research was developed in a Brazilian public institution of higher education, in the process of internationalization, the Federal University of Espírito Santo (Ufes). For that purpose, 20 technical administrative processes for formalization of general agreements for international academic cooperation signed by Ufes through its International Office were analyzed. It is a qualitative, descriptive, documentary research. From the analysis, it was possible to observe that the lack of standardization of the documents was a delay factor in the procedure of conclusion of general agreements for international academic cooperation at Ufes, due to the complexity of the process, which includes bilingual official documents. To answer the main question proposed, through the analysis of the agreements processes of Ufes and other Brazilian public higher education institutions, plus the relevant national legislation, the delivered technical product was a compilation of documentary standards and technical-administrative procedure flows, with their textual and translation models of the main languages of partner countries. For future work, there is a need for a broader assessment of procedural and documentary models nationally and internationally, as well as their variations; also, the evaluation of the application of the technical product developed in this work is an opportunity for further research.